The effect of design shape factor on the combustion parameters of rotary engine - Smail, Boughou (Kulliyyah of Engineering, International Islamic University Malaysia, 2019)
Comparatively, this research is motivated to investigate, through simulation, the Wankel engine performance and to focus on possible developments studies of rotary engine design. The controversial rotary engine produces a direct rotational motion. The triangular rotor shape which Felix Wankel derived from the Reuleaux triangle of complex geometry rotates continuously by keeping contact with its housing in three points separating the chambers into three where the different conventional 4-strokes occur. Near the top dead centre TDC where the volume of the chamber is minimal, critical performance of the mixture combustion is related to the shape of the chamber. An investigation of the shape factor effect on the combustion parameters of the rotary engine performance by simulation of compressible flow field in rotary engine's combustion chamber by applying the technique of Dynamic Mesh in CONVERGE CFD. In function of crankshaft angles, the change of flow field streamline, temperature and pressure of the volume is investigated. The results showed that a constantly changing swirl was formed in the combustion chamber during the intake and compression strokes near TDC as a result of the combined effects of the pocket of the rotor and the swirls in the combustion chamber. The very low compression ratio would yield a poor Otto-cycle thermal efficiency. The compression ratio could be increased by increasing e/R, but it would still be low for most applications. It is therefore important to consider the favorable influence of flank rounding on rotary engine performance. Moreover, the flow behaviour during the exhaust stroke where the propagation of burned gases escapes towards the intake port chamber even though a perfect sealing was assumed. This propagation can be of an interest investigation for researchers to find the suitable possible epitrochoid shape.